Vulnerability Dynamics and Urban Flood Hazardscape Pattern: A Geospatial Analysis in Gombe City, Nigeria - Faiza Mahdi Doho; Julius Afolabi Falola; Sulaiman Yunus (Geosfera Indonesia, 2022)
In many Nigerian states, urban flooding has resulted into the death of numerous people and destruction of properties worth billions of Naira. This study examined the vulnerability dynamics and urban flood hazardscape pattern within Gombe city with a view to providing bases for policy formulation (where necessary), enforcement and decision making on flood risk reduction for enable sustainable urban development. ASTER DEM and Landsat images (2000, 2010 and 2019) was used to generate Digital Terrain Model (DTM) and impervious surface areas. Rainfall data for 2000-2018 was used to examine rainfall trend using regression analysis. The result revealed that flood hazardscape and vulnerability dynamics are largely influenced by physical and social factors. The results for vulnerability dynamics shows that as at 2000, about 1.4km2 lies on the relatively low vulnerable area,4.1km2falls within the moderate, and about 14.6km2 falls on critical area. By 2010, only about 1km2 lies on the relatively low area, 5.2km2 occupied the moderate and about 15km2was found within the critically vulnerable area. In 2019, the vulnerability dynamics depicts that about 33.4km2, impervious surface (builtup area) existed, out of which 2.8km2 lies on the low vulnerable area, 9.4km2 on the moderately vulnerable and 21.2km2 in critically vulnerable areas. It is concluded that flood hazardscape and vulnerability dynamics in Gombe city is influenced by both physical and anthropogenic factors. It is recommended that planning departments should put into consideration urban flood hazardscape maps for future development so as to reduce the risk and control future exposure flood impact. Keywords : Impervious surfaces; Feature extraction; Hazardscape; Urban flood; Vulnearbility dynamics Copyright (c) 2022 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License